2019
DOI: 10.1111/ijac.13434
|View full text |Cite
|
Sign up to set email alerts
|

Waste glass in civil engineering applications—A review

Abstract: Each year, hundreds of thousands of tons of industrial wastes are being stockpiled, landfilled, and disposed of in storages occupying large areas of land that would otherwise be available for productive use. Recycling of such wastes is now becoming of urgent global interest due to an increasing population, the rise in anthropogenic activities, and the need for more efficient resource and waste management systems.Among many wastes, the generation of glass is dramatically increasing, particularly in the municipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 133 publications
(234 reference statements)
0
14
0
1
Order By: Relevance
“…There are some review studies on WG incorporated concrete [ 28 , 29 , 30 ], but most of those are focused on the mechanical properties of cement-based concrete. In those published review papers, the effect of particle size and amount of glass on the physical and mechanical properties of WG concrete are described.…”
Section: Introductionmentioning
confidence: 99%
“…There are some review studies on WG incorporated concrete [ 28 , 29 , 30 ], but most of those are focused on the mechanical properties of cement-based concrete. In those published review papers, the effect of particle size and amount of glass on the physical and mechanical properties of WG concrete are described.…”
Section: Introductionmentioning
confidence: 99%
“…Отчасти, эту проблему решает переработка различных отходов в строительные материалы. Перерабатывают всё: ТБО, отходы промышленности, остатки вышедших из эксплуатации и, как следствие, разрушенных зданий и сооружений [20][21][22]. Этой теме посвящено множество научных статей и трудов [23][24][25].…”
Section: результаты исследования и их обсуждениеunclassified
“…One of the ways of reducing the consumption of natural sand is to utilise wastes as an alternative material (Emery, 1974). Recycling of wastes could reduce the demand for virgin natural resources and help to dispose of them effectively (Kazmi et al, 2019b). The volumes of wastes generated each year are alarmingly increasing due to a rise in the global population.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2020) explored the fire resistance performance of cementitious composites containing CWG. Several studies have shown that CWG may be partially used as supplementary cementitious material and alternative to fine-grained aggregates in concrete production (Kazmi et al, 2019b). These applications, among others, typically utilise only some of the CWG produced (generally less than 40%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation